The Hsp90 Co-chaperones Sti1, Aha1, and P23 Regulate Adaptive Responses to Antifungal Azoles - Gu, Xiaokui; Xue, Wei; Yin, Yajing; Liu, Hongwei; Li, Shaojie; Sun, Xianyun (Frontiers in Microbiology, 2016)
Heat Shock Protein 90 (Hsp90) is essential for tumor progression in humans and drug resistance in fungi. However, the roles of its many co-chaperones in antifungal resistance are unknown. In this study, by susceptibility test of Neurospora crassa mutants lacking each of 18 Hsp90/Calcineurin system member genes (including 8 Hsp90 co-chaperone genes) to antifungal drugs and other stresses, we demonstrate that the Hsp90 co-chaperones Sti1 (Hop1 in yeast), Aha1, and P23 (Sba1 in yeast) were required for the basal resistance to antifungal azoles and heat stress. Deletion of any of them resulted in hypersensitivity to azoles and heat. Liquid chromatography–mass spectrometry (LC-MS) analysis showed that the toxic sterols eburicol and 14α-methyl-3,6-diol were significantly accumulated in the sti1 and p23 deletion mutants after ketoconazole treatment, which has been shown before to led to cell membrane stress. At the transcriptional level, Aha1, Sti1, and P23 positively regulate responses to ketoconazole stress by erg11 and erg6, key genes in the ergosterol biosynthetic pathway. Aha1, Sti1, and P23 are highly conserved in fungi, and sti1 and p23 deletion also increased the susceptibility to azoles in Fusarium verticillioides. These results indicate that Hsp90-cochaperones Aha1, Sti1, and P23 are critical for the basal azole resistance and could be potential targets for developing new antifungal agents.